Bacterial and Parasitic Pathogens as Risk Factors for Cancers in the Gastrointestinal Tract: A Review of Current Epidemiological Knowledge - Duijster, Janneke W.; Franz, Eelco; Neefjes, Jacques; Mughini-Gras, Lapo (Frontiers in Microbiology, 2021)
The oncogenic potential of viral infections is well established and documented for many years already. However, the contribution of (commensal) bacteria and parasites to the development and progression of cancers has only recently gained momentum, resulting in a rapid growth of publications on the topic. Indeed, various bacteria and parasites have been suggested to play a role in the development of gastrointestinal cancer in particular. Therefore, an overview of the current epidemiological knowledge on the association between infections with bacteria and parasites and cancers of the gastrointestinal tract is needed. In this review, we summarized the methodological characteristics and main results of epidemiological studies investigating the association of 10 different bacteria (Bacteroides fragilis, Campylobacter spp., Clostridium spp., Enterococcus faecalis, Escherichia coli, Fusobacterium nucleatum, Porphyromonas gingivalis, nontyphoidal Salmonella, Salmonella Typhi, and Streptococcus spp. ) and three parasites (Cryptosporidium spp., Schistosoma spp. and Strongyloides stercoralis) with gastrointestinal cancer. While the large body of studies based on microbiome sequencing provides valuable insights into the relative abundance of different bacterial taxa in cancer patients as compared to individuals with pre-malignant conditions or healthy controls, more research is needed to fulfil Koch’s postulates, possibly making use of follow-up data, to assess the complex role of bacterial and parasitic infections in cancer epidemiology. Studies incorporating follow-up time between detection of the bacterium or parasite and cancer diagnosis remain valuable as these allow for estimation of cause-effect relationships.